Políticas públicas e estratégias camponesas: entre a produção e a reprodução social - Fernandes, Marina (Universidade Federal de São Carlos, 2023)
This research project focuses on analyzing the present of public policy aimed at family agriculture and the conditions of the peasantry stemming from a case study located at the municipality of Ribeirão Preto, called Sustainable Development Project (PDS) of Barra. We are interested to know the impacts on the strategies of agricultural production and peasant social reproduction in the face of the Food Acquisition Program changes in this settlement, and, according to these changes, understand how they change (or not) the peasant own condition of the Barra PDS settlers, which is characterized, ultimately, by the understanding of the land as a space that generates life and dignifies the work of the settlers. In this regard, what we address in this work is one of the central elements for contemporary rural development: the agrarian question present in the dialogue between the settlements and the State.
Public policies and peasant strategies: between production and social reproduction
Keywords: Questão agrária; Programa de aquisição de alimentos; Campesinato; Agrarian question; Public Policy; Food acquisition program; Peasant; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA RURAL